2004
DOI: 10.1002/adfm.200305050
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Low‐κ Polyimide Films via Poly(amic acid)s with Grafted Poly(ethylene glycol) Side Chains from a Reversible Addition–Fragmentation Chain‐Transfer‐Mediated Process

Abstract: Thermally‐initiated living radical graft polymerization of poly(ethylene glycol) methyl ether methacrylate (PEGMA) with ozone‐pretreated poly[N,N′‐(1,4‐phenylene)‐3,3′,4,4′‐benzophenonetetra‐carboxylic amic acid] (PAmA) via a reversible addition–fragmentation chain‐transfer (RAFT)‐mediated process was carried out. The chemical compositions and structures of the copolymers were characterized by nuclear magnetic resonance (NMR) spectroscopy, thermogravimetric analysis (TGA), X‐ray photoelectron spectroscopy (XPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 31 publications
(11 reference statements)
1
34
0
Order By: Relevance
“…Moreover, the dielectric constant of the sample with 20 wt.-% mica content is nearly the same as that of layered silicates/fluorinated PI hybrid films [24] and also higher than that of cross-linked PI structures. [9,11] Figure 3 shows the dependence of the dielectric constant of PI-mica hybrid films with different mica contents on the frequency at À130 8C [ Figure 3(a)] and 140 8C [ Figure 3(b)]. The general trend deduced from Figure 3 shows that there is a relatively higher dielectric constant at low frequency, and the dielectric constant decreases slowly with increasing frequency.…”
Section: Ftir Spectrum and Xrd Patternsmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, the dielectric constant of the sample with 20 wt.-% mica content is nearly the same as that of layered silicates/fluorinated PI hybrid films [24] and also higher than that of cross-linked PI structures. [9,11] Figure 3 shows the dependence of the dielectric constant of PI-mica hybrid films with different mica contents on the frequency at À130 8C [ Figure 3(a)] and 140 8C [ Figure 3(b)]. The general trend deduced from Figure 3 shows that there is a relatively higher dielectric constant at low frequency, and the dielectric constant decreases slowly with increasing frequency.…”
Section: Ftir Spectrum and Xrd Patternsmentioning
confidence: 82%
“…[5] Previous reports showed that low dielectric constant of polymer materials could be achieved by incorporating ZnO inorganic filler [4,6] and by having large substituent groups, cross-linked PI or perfluoro groups. [7][8][9][10][11][12][13] Recent development in layered silicates/PI composites indicates that these composites possess excellent mechanical properties, thermal stability, and gas barrier properties. [14][15][16][17][18][19][20][21] Mica is a natural mineral with good electrical and thermal insulating properties.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the morphological structure of porous PI was determined by the initial morphology of the microphase separated structures of the copolyimides [17]. But the decomposition technique could plasticize the PI and generate the chain mobility during the pore formation, which made the pores collapse, particularly when the processing temperature is too close to the softening temperature (the minimum temperature of glass transition) of the PIs [18,19]. Furthermore, thermal degradation is adverse to the molecular weight and certain critical mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Yet another approach to the preparation of nanoporous low-PI films was via thermally-induced graft copolymerization of poly(amic acid) with a vinyl monomer, followed by side chain decomposition after thermal imidization. [23][24][25] One class of the inorganic component-polyhedral oligomeric silsesquioxanes (POSS), e.g., the octameric form (R 7 RЈSi 8 O 12 ) consists of a rigid cubic silica core and a nanopore of about 0.3-0.4 nm in size. 26 Polymer films based on polysilsesquioxanes with low-has been prepared.…”
Section: Introductionmentioning
confidence: 99%